2023
DOI: 10.3390/nu15173679
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Role of Orexin in the Regulation of REM Sleep and Appetite

Maria P. Mogavero,
Justyna Godos,
Giuseppe Grosso
et al.

Abstract: Orexin plays a significant role in the modulation of REM sleep, as well as in the regulation of appetite and feeding. This review explores, first, the current evidence on the role of orexin in the modulation of sleep and wakefulness and highlights that orexin should be considered essentially as a neurotransmitter inhibiting REM sleep and, to a much lesser extent, a wake promoting agent. Subsequently, the relationship between orexin, REM sleep, and appetite regulation is examined in detail, shedding light on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…The LH coordinates sleep-promoting activities, and disruptions in orexin function may upset the delicate balance between sleep and wakefulness, thereby contributing to a spectrum of sleep-related problems [36][37][38]. This emphasizes the importance of investigating the role of the LH and orexin in comprehending and addressing sleep-related disturbances [33,38]. We found that GBL decreased expression of Orexin positive cells in the LH region.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The LH coordinates sleep-promoting activities, and disruptions in orexin function may upset the delicate balance between sleep and wakefulness, thereby contributing to a spectrum of sleep-related problems [36][37][38]. This emphasizes the importance of investigating the role of the LH and orexin in comprehending and addressing sleep-related disturbances [33,38]. We found that GBL decreased expression of Orexin positive cells in the LH region.…”
Section: Discussionmentioning
confidence: 71%
“…Orexin neurons are characterized by wakefulness-promoting activity, reaching peak firing rates during wakefulness [32][33][34], and exhibiting the highest extracellular levels of orexin during wakefulness [35]. The LH coordinates sleep-promoting activities, and disruptions in orexin function may upset the delicate balance between sleep and wakefulness, thereby contributing to a spectrum of sleep-related problems [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, leptin is an anorexigenic adipose hormone. Therefore, a plausible explanation for the increases in WASO and cortical arousal is that, in LEA states, orexigenic signals could be activated in the brain, promoting wakefulness and inducing fragmented sleep and early awakening [ 49 ]. A previous study by Falkenberg et al [ 50 ] observed an inverse association between the length of the last meal to bedtime window and sleep duration in professional rugby players during intensive training, suggesting that early awakening could result from low energy flux and higher hunger sensations.…”
Section: Discussionmentioning
confidence: 99%
“…They are lacking in patients with narcolepsy type 1 (NT1). The fact that SRED is frequent in NT1 [31] indicates that orexin may also play a role in SRED. It needs to be emphasized that most previous studies were carried out in NES but not in patients with SRED, because of the lack of clear distinction between the two disorders [2].…”
Section: Pathomechanism 81 Is Sred a Neuroendocrine Disorder?mentioning
confidence: 99%